Unfulfilled promises of equity: racism and interculturalism in Chilean education. Issue 6 (1st November 2016) - Webb, Andrew; Radcliffe, Sarah
Abstract: In rural Araucanía secondary schools, prescriptive and formal government programs for interculturalism – designed to overcome differentials between Indigenous and non-Indigenous pupils in educational outcomes – have had limited impact. Drawing on research across four schools, this article examines how the dynamics between state-led top-down prescriptive guidelines interface with teacher practice, school objectives, and existing racializing dynamics to produce diverse educational outcomes. Drawing on in-depth qualitative research involving over 100 pupils and teachers, this article identifies two key in-school processes that work to undercut official policy effectiveness. First, state policies do little to challenge staff and institutionalized racism, thereby perpetuating the marking of Indigenous pupils as Other. Combined with lack of political will and resources for teacher training and lesson preparation, this leaves educational inequalities in place. Second, the institutional allocation of time and resources to intercultural education reinforces widespread devaluation of indigenous knowledge among teachers, educators and public opinion. Nevertheless, the study also found that in certain schools these conditions did not prevent the adoption of pedagogies that affirmed Indigenous difference and challenged the dominance of whiteness. Informed by a critical theorization of the power and unmarked nature of racial inequality, this article argues that whiteness is neither recognized nor challenged in rural secondary schools in southern Chile, despite its ubiquity and pervasive influence on curriculum, pedagogies and institutional arrangements.